Example of article 21 income tax calculation on employees: Case study at PT Asuransi Ramayana Manado Branch - Mustaqfiroh, Novi Kholifatul; Rosida, Alfiyah Fajar; Sonia, Lailatul Izzah; Hanifah, Nurul (Maliki Interdisciplinary Journal, 2024)
Taxes are one of Indonesia’s largest sources of income. Domestic taxes are classified by the government into various forms of taxes levied on the basis of ownership of assets from the taxpayer. Article 21 of the VAT refers to income tax on work, services and activities carried out by individual taxpayers of domestic persons. The method used in this article is library research. The result of the calculation can be concluded that there is a difference in the total tax owed according to PT. Ramyana Insurance and Tax Act.